Simple indicators are good proxies for ecological complexity when assessing Atlantic Forest restoration success - Massi, Klécia G. [UNESP]; Chaves, Rafael B.; Tambosi, Leandro R. (Wiley, 2022)
Legal regulation related to restoration monitoring should be supported and validated by studies that evaluate the performance of indicators. In Brazil, a specific state regulation uses three indicators to attest recovery: ground cover with native vegetation (i.e. canopy cover, for tropical forest restoration projects) and density and richness of native plants spontaneously regenerating. Thus, we adopted other three ecological parameters: richness of zoochorous regenerant species (a functioning indicator linked to seed dispersal), the density of non-pioneer regenerants (a composition indicator), and dominance (a structure indicator), to test whether the indicators of the legal state monitoring protocol were associated to these more qualified indicators and we discussed the state protocol effectiveness. We evaluated 10 sites under restoration in the Atlantic Forest ranging from 9 to 45 years old and a reference area. Our results showed that the three indicators of the state monitoring protocol were associated to more qualified indicators in different restored sites and they can be considered proxies of ecological parameters to monitor and attest restoration success of tropical rainforest. In addition, dominance was strongly associated with richness of regenerants, but it was not associated to density, implying that richness and density of regenerants are not redundant and both should be monitored in the field. This kind of analysis could be usefully applied to define powerful and integrative indicators elsewhere, simplifying them without losing effectiveness as a means to stimulate wide adoption of monitoring protocols in the UN Decade on Ecosystem Restoration.
Keywords: ecological restoration; indicators; monitoring protocol; natural regeneration; passive restoration; policy; tropical forest